1989
DOI: 10.1038/hdy.1989.109
|View full text |Cite
|
Sign up to set email alerts
|

The direction of pollen flow between two co-occurring rice species, Oryza sativa and O. glaberrima

Abstract: Two cultivated rice species, Oryza sativa L. and 0. glaberrima Steud., are often grown mixed in farmers' fields in West Africa. Two sympatric species were collected from two different fields. The frequency of interspecific hybridization between the two species was estimated from the seeds harvested in farmers' fields and in artificial mixtures. The two species were isolated by prezygotic isolating barriers such as autogamy and differences in time of flowering, however, the isolation was incomplete. The frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Wild relatives usually store great amounts of genetic variation (Clegg, Brown, and Whitfield, 1984;Doebley, 1989;Schmit and Debouck, 1991), which may be of present or future interest for plant improvement programs (Miranda-Colin, 1967, 1979Frankel and Soule, 1981;Brown and Clegg, 1983); they can provide information regarding the process ofdomestication (Harlan, 1975;Doebley, 1989) and may represent actual or potential weeds, especially in the face of gene flow with genetically engineered relatives (Doebley, 1989;Ellstrand and Hoffman, 1990;Ellstrand, 1992). On the other hand, the wild relatives illustrate how the different evolutionary forces can operate even in the presence ofstrong (artificial) selection (Sano, 1989;Ellstrand, 1992).…”
mentioning
confidence: 99%
“…Wild relatives usually store great amounts of genetic variation (Clegg, Brown, and Whitfield, 1984;Doebley, 1989;Schmit and Debouck, 1991), which may be of present or future interest for plant improvement programs (Miranda-Colin, 1967, 1979Frankel and Soule, 1981;Brown and Clegg, 1983); they can provide information regarding the process ofdomestication (Harlan, 1975;Doebley, 1989) and may represent actual or potential weeds, especially in the face of gene flow with genetically engineered relatives (Doebley, 1989;Ellstrand and Hoffman, 1990;Ellstrand, 1992). On the other hand, the wild relatives illustrate how the different evolutionary forces can operate even in the presence ofstrong (artificial) selection (Sano, 1989;Ellstrand, 1992).…”
mentioning
confidence: 99%
“…Compared to the Asian species, O. glaberrima is characterized by its red hulls, small size, smooth glumes and tendency to break in mechanized milling (Carney, 1998). Because O. glaberrima does not readily cross with O. sativa, the African rice's greater tolerance to salinity, drought, and flooding is receiving increasing plant breeding attention (Sano, 1989;Harlan, 1995). However, the real beginning of the valorization of O. glaberrima genetic potential in the varietal improvement programs with the Asian cultivated rice has started by Africa Rice Center (AfricaRice, formerly WARDA) through the development of interspecifics varieties called and trademarked under the name Nerica: New Rice for Africa (Jones et al, 1997;Sie et al, 2005;Somado et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial backcrosses produced fertile progenies which resembled the parental phenotypes, indicating that under natural conditions it is difficult to detect hybrid derivatives [9], [14]. Given that the hybrid group (cluster 4) is closer to O. sativa than to O. glaberrima , successful backcrossing events in the field to O. sativa might be more likely than to O. glaberrima .…”
Section: Discussionmentioning
confidence: 99%
“…However, some scientists suggested that introgression between the two rice species occurs in the field [7] , [8] . Based on experiments, Sano [9] argued that pollen flow occurs mainly from O. sativa to O. glaberrima . Other experimental studies showed that introgression from O. glaberrima to O. sativa is possible, although at a low frequency [10] [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation